A New Steroidal Saponin from Trichosanthes dioica (Roxb.) - Saxena, V.K.; Dave, R.K. (Asian Journal of Chemistry, 2010)
A new steroidal saponin 24-α-ethyl-20-ene-7-hydro-stigmast-8β:14β-di-3-O-β-D-xylofuranoside 1 has been isolated from MeOH soluble fraction of 95% EtOH extract of the leaves of Trichosanthes dioica.